2019
DOI: 10.1002/anie.201907298
|View full text |Cite
|
Sign up to set email alerts
|

Observing the Reversible Single Molecule Electrochemistry of Alexa Fluor 647 Dyes by Total Internal Reflection Fluorescence Microscopy

Abstract: Alexa Fluor 647 is a widely used fluorescent probe for cell bioimaging and super‐resolution microscopy. Herein, the reversible fluorescence switching of Alexa Fluor 647 conjugated to bovine serum albumin (BSA) and adsorbed onto indium tin oxide (ITO) electrodes under electrochemical potential control at the level of single protein molecules is reported. The modulation of the fluorescence as a function of potential was observed using total internal reflectance fluorescence (TIRF) microscopy. The fluorescence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Gooding and co-workers have documented the electrochemical reduction of Alexa 488 and accompanying uorescence quenching over most of the negative portions of the potential range explored here. 32 We attribute the modest increase in emission intensity observed at the most negative potentials in Fig. 5 to a small population of unreacted Alexa 488 whose intensity is enhanced by interaction with an H 2 nanobubble, thus supporting the formation of nanobubbles even under these conditions, which mitigate against uorescence.…”
Section: H 2 Nanobubble Formationmentioning
confidence: 61%
“…Gooding and co-workers have documented the electrochemical reduction of Alexa 488 and accompanying uorescence quenching over most of the negative portions of the potential range explored here. 32 We attribute the modest increase in emission intensity observed at the most negative potentials in Fig. 5 to a small population of unreacted Alexa 488 whose intensity is enhanced by interaction with an H 2 nanobubble, thus supporting the formation of nanobubbles even under these conditions, which mitigate against uorescence.…”
Section: H 2 Nanobubble Formationmentioning
confidence: 61%
“…In single-molecule fluorescence spectroscopy/imaging, a stepwise change in a fluorescence intensity [increase or decrease (bleaching)] has been reported in various chemical and biological systems and is known to be one of the important characteristics of single-molecule spectroscopy/imaging. Thus, the stepwise and almost constant increment of I RhB with t in Figure c demonstrates laser-induced simultaneous single-molecule extraction and detection of RhB in the aqueous PNIPAM/BuOH solution. At [RhB] = 10 –14 M [six RhB molecules in (100 × 100 × 100) μm 3 ], one RhB molecule occupies ∼(40 × 40 × 40) μm 3 and this corresponds to the situation that a PNIPAM/BuOH microparticle with d = ∼5 μm sits in the center of a (40 × 40 × 40) μm 3 volume that is surrounded by one RhB molecule: see Figure d.…”
Section: Resultsmentioning
confidence: 99%
“…Interfacial and intracellular redox states and processes have been extensively explored using fluorescent probes of redox proteins and dyes, where mapping redox potentials (times) of interfacial and intracellular electron transfer processes in chemical and biological systems have become feasible due to recent technological developments. In contrast to conventional single-molecule confocal fluorescence microscopy, which only detects one single molecule at a time due to its limitation of a single point photon detector, single-molecule localization super-resolution fluorescence microscopy allows simultaneous fluorescence monitoring of multiple single molecules in the field of view by high-speed camera with high sensitivity, and thereby hundreds of single-molecule fluorescence intensity trajectories can be acquired with high throughput. For more than a decade, single-molecule fluorescence microscopies have been combined with electrochemical modulation to develop single-molecule spectroelectrochemistry at single-molecule levels and nanoscales. For example, heterogeneous charge mobility of individual conjugated polyelectrolyte nanoparticles was studied in organic solvent via two-color single particle spectroelectrochemistry; Jin et al reported the direct observation and quantitative analysis of single redox events of resorufin to the nonfluorescent dihydroresorufin via electrochemical modulation inside silica nanochannels . The modulation of the fluorescence as a function of electrochemical potential of the fluorescent dye Alexa Fluor 647 conjugated to bovine serum albumin was studied by total internal reflection fluorescence microscopy .…”
Section: Introductionmentioning
confidence: 99%
“…reviewed single-molecule fluorescence microscopy for probing the electrochemical interface . When the single-molecule fluorescence microscope is coupled with electrochemical potential scanning, every redox-active single fluorescent molecule is expected to be laid out in an electrochemically modulated fluorescence intensity (vs time) trajectory. However, photodriven processes also cause single molecule fluorescence intensity fluctuations, which disguise the electrochemically driven fluorescence intensity changes. In other words, it is difficult to tell the electrochemically modulated fluorescence change apart from other causes of fluorescence on/off blinking.…”
Section: Introductionmentioning
confidence: 99%